Implementasi Kebijakan Reforma Agraria Di Kecamatan Jenawi Kabupaten Karanganyar (Studi Asset Reform Dan Acces Reform) - Sularna & Joko Suranto (Master of Public Administration, Universitas Slamet Riyadi, 2016)
Land reform is the Agrarian Reform Program launched by the IndonesianGovernment. The program is implemented for the structural arrangement ofdomination and ownership of the land. This is done to ensure the right toagrarian resources through land reform or asset reform and broaderdevelopment efforts which involves multiple participants to ensure that theland assets that have been given can grow productively and sustainably oraccess reform.The purpose of this study was to describe the implementation of agrarianreform policy in the district Jenawi, Karanganyar. The importance ofachieving the goal of this study was that the success of an activity isdetermined by the quality of the process and indicators that have been set.This study was descriptive kualitatf research which combines theimplementation model of Donald S. Van Meter, Carl E. Van Horn, andEdward III. Data collection techniques that used in this study was interviewsand review of document. Determination of informants by using purposivesampling. Informants in this study came from Land Agency Office ofKarangayar, the District Head Jenawi, and the villager of Anggrasmanis.Based on the study results, it was concluded that agrarian reform policieshave been implemented properly in District Jenawi, Karanganyar. Bothimplementers and the target group in these activities have known andunderstand the standards and target activities. Land Agency Office ofKaranganyar still understaffed of gauge in terms of implementation of assetreform. This is because the number of employees of measure is notcomparable with the land area that must be done. Meanwhile, in the termsof implementation of acces reform, human resources which is own isconsidered to be adequate.Mentoring and counseling to the community programs that has beenprepared can be done well and get a positive response from the targetgroup, so it can be formed a good cooperation. A positive attitude shown bythe whole range of implementers, so that a positive response was alsoobtained from the target group. Agrarian reform activities in the district ofJenawi Karanganyar has accordance with Budget ImplementationRegistration Form 2014, the technical instructions, and legislation whichserve as guidelines. The purpose of agrarian reform in the District Jenawiespecially the Village Anggrasmanis has been perceived by society as wellas a positive impact in their lives.Key words: Standards and Objectives Policy, Resonances, Communication,Disposition, Bureaucratic structure.